Persistent centripetal fat distribution and metabolic abnormalities in patients in long‐term remission of Cushing's syndrome. (4th December 2014) - Wagenmakers, Margreet; Roerink, Sean; Gil, Linda; Plantinga, Theo; Smit, Jan; Netea‐Maier, Romana; Hermus, Ad
Summary Objective Centripetal obesity is associated with systemic low‐grade inflammation and an increased cardiovascular risk. Patients in long‐term remission of Cushing's syndrome (CS) report persisting abdominal fat accumulation. However, this has previously not been adequately objectified. Therefore, we investigated the adipose tissue distribution and adipocytokine profiles of patients in long‐term remission of CS. Design Cross‐sectional case–control study in a tertiary referral centre. Patients Fifty‐eight patients, in remission of CS for at least 5 years, were compared to 58 age‐, gender‐ and BMI‐matched healthy control subjects. Measurements Measures of body composition (assessed with clinical evaluation and dual‐energy X‐ray absorptiometry (DEXA) scanning) and serum adipocytokine profiles. Results Compared to the matched control subjects, patients in long‐term remission of CS had a greater waist circumference (P < 0·01), a smaller thigh circumference (P < 0·01), a higher waist‐to‐hip ratio (P < 0·01) and a higher hip‐to‐thigh ratio (P < 0·01). As measured with DEXA scanning, patients had a higher percentage of truncal fat mass (P = 0·01), and the truncal fat mass to leg fat mass ratio was greater (P < 0·01). Patients had lower adiponectin levels (P < 0·01), higher leptin levels (P < 0·01) and higher resistin levels (P = 0·04) than control subjects. Conclusion Even after long‐term remission, patients who suffered from CS in the past continue to have a centripetal adipose tissue distribution and an adverse adipokine profile. This is independent of aetiology of the CS, treatment strategies, hormonal deficiencies and comorbidity, and probably contributes to the persistent increased cardiovascular risk.